Novel PDMS-b-PPO Membranes Modified with Graphene Oxide for Efficient Pervaporation Ethanol Dehydration - Mariia Dmitrenko; Anastasia Chepeleva; Vladislav Liamin; Anna Kuzminova; Anton Mazur; Konstantin Semenov; Anastasia Penkova (Membranes, 2022)
Purification and concentration of bioalcohols is gaining new status due to their use as a promising alternative liquid biofuel. In this work, novel high-performance asymmetric membranes based on a block copolymer (BCP) synthesized from polydimethylsiloxane (PDMS) and poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) were developed for enhanced pervaporation dehydration of ethanol. Improvement in dehydration performance was achieved by obtaining BCP membranes with a “non-perforated” porous structure and through surface and bulk modifications with graphene oxide (GO). Formation of the BCP was confirmed by Fourier-transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies. The changes to morphology and physicochemical properties of the developed BCP and BCP/GO membranes were studied by scanning electron (SEM) and atomic force (AFM) microscopies, thermogravimetric analysis (TGA) and contact angle measurements. Transport properties of the developed membranes were evaluated by the pervaporation dehydration of ethanol over a wide concentration range (4.4–70 wt.% water) at 22 °C. The BCP (PDMS:PPO:2,4-diisocyanatotoluene = 41:58:1 wt.% composition) membrane modified with 0.7 wt.% GO demonstrated optimal transport characteristics: 80–90 g/(m2h) permeation flux with high selectivity (76.8–98.8 wt.% water in the permeate, separation factor of 72–34) and pervaporation separation index (PSI) of 5.5–2.9.